Protective Role of the Nucleic Acid Sensor STING in Pulmonary Fibrosis - Savigny, Florence; Schricke, Corinne; Lacerda-Queiroz, Norinne; Meda, Mélanie; Nascimento, Mégane; Huot-Marchand, Sarah; Da Gama Monteiro, Felipe; Ryffel, Bernhard; Gombault, Aurélie; Le Bert, Marc; Couillin, Isabelle; Riteau, Nicolas (Frontiers in Immunology, 2021)
Idiopathic pulmonary fibrosis (IPF) is the most common and severe type of interstitial lung disease for which current treatments display limited efficacy. IPF is largely driven by host-derived danger signals released upon recurrent local tissue damage. Here we explored the roles of self-DNA and stimulator of interferon genes (STING), a protein belonging to an intracellular DNA sensing pathway that leads to type I and/or type III interferon (IFN) production upon activation. Using a mouse model of IPF, we report that STING deficiency leads to exacerbated pulmonary fibrosis with increased collagen deposition in the lungs and excessive remodeling factors expression. We further show that STING-mediated protection does not rely on type I IFN signaling nor on IL-17A or TGF-β modulation but is associated with dysregulated neutrophils. Together, our data support an unprecedented immunoregulatory function of STING in lung fibrosis.